Debate: TAVI prosthesis selection for severe calcification. The balloon-expandable technology approach - Cristóbal A. Urbano-Carrillo (REC: Interventional Cardiology (English Ed.))
QUESTION: What are the implications of aortic valve calcification on the outcomes of transcatheter aortic valve implantation (TAVI)? ANSWER: Aortic valve calcification has, undoubtedly, been a major influence on TAVI outcomes and the evolving design of heart valves. Severe calcification has been associated with an increased likelihood of complications or poor outcomes, particularly in terms of residual paravalvular leak, need for postoperative pacemaker implantation, or aortic annular rupture, among others.1 Several generations of TAVI prostheses have mainly evolved with the aim of reducing paravalvular leak,2 through the use of skirts and coverings that facilitate sealing by adapting to the irregularities caused by annular and outflow tract calcifications. The goal is to balance sealing capacity with the optimal radial force needed, preventing excessive force that could cause conduction disturbances or, more critically, annular rupture. This emphasizes the critical role of procedural planning, which must account for the extent of calcification in all affected tissues. This meticulous planning, combined with experienced judgment and a deep understanding of the behaviour of each prosthesis is crucial for selecting the correct valve size. Q.: What morphological and quantitative aspects of valvular calcification do you assess at your center? A.: In addition to the usual annular measurement, in patients...